Assessment of the impact of climate and non-climatic parameters on cocoa production: a contextual analysis for Cameroon - Bomdzele, Eric; Molua, Ernest L. (Frontiers in Climate, 2023)
Agriculture remains the mainstay of Cameroon's economy, with cocoa as one of its key export commodities. However, cocoa production may be affected by climate-related stressors. This study assesses the influence of climate and non-climate parameters on cocoa performance in Cameroon. We use time series data for temperature, rainfall, carbon dioxide emission, land use, labour hours, pesticide application, and cocoa output in Cameroon spanning 60 years (1961 to 2021). Trend analyses reveal the stochastic response of crop production under climate variation. Leveraging the perennial crop supply response framework, a Vector Error Correction Model (VECM) reveals short-term climate impacts on cocoa production. The econometric estimation shows that climate and non-climate parameters explain the variations in cocoa output. More specifically, the short-run results reveal that temperature, carbon dioxide emission, land use, and pesticide quantity significantly increase crop yield, whereas rainfall decreases it substantially. Furthermore, the long-run analysis indicates that temperature, rainfall, carbon dioxide emission, and land use are significant negative determinants of the yearly changes in cocoa output. We recommend government policy reforms which address access to land, subsidies, and improved production technologies to reduce greenhouse gas emissions and enhance farmers' adaptive capacities to climatic stressors.